One-to-many reversible mapping for IPV6 address generation: Simulation software development - Hakiem, Nashrul; Siddiqi, Muhammad Umar (Little Lion Scientific Islamabad Pakistan, 2013)
This paper presents the development of a one-to-many reversible mapping mechanism simulation for IPv6 address generation. The aim of this mechanism is to improve IPv6 addresses generation in terms of privacy and security in an enterprise local area network (LAN). Each time a user accesses a network, a dynamic IPv6 address is assigned via the DHCPv6 server. The dynamic address (one-to-many mapping) is to protect a user from unwanted behavior analysis attempting to exploit IPv6 addresses, thus protecting user privacy. However, the dynamic address can be uniquely linked to the user (many-to-one mapping) if the need arises. The one-to-many reversible mapping is generated dynamically using Cipher Feedback (CFB) mode of operation of the Advanced Encryption Standard (AES). Software simulation is developed using the software engineering waterfall model and a Unified Modeling Language (UML) class diagram as a notation. The results show that the mechanism simulates well for IPv6 address generation and IPv6 address owner identification. The one-to-many mapping may be incorporated into DHCPv6 software and many-to-one mapping may be implemented as a complement of local area network monitoring software.